The Effect of Communicative Language Teaching (CLT) Method on Speaking Ability and Speaking Anxiety - Andi Sutanto; Hasbi Sjamsir; Susilo (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
This research aims to know the effect of Communicative Language Teaching (CLT) method on speaking ability and speaking anxiety of police brigadier students at police state school of East Kalimantan Regional Police. The research has been conducted through true experimental research design. The result of this research revealed that Communicative Language Teaching (CLT) method affected speaking ability and speaking anxiety of the students at Police State School of East Kalimantan Regional Police in academic year 2021/2022. The alternative hypothesis (Ha) of this study was accepted because the result of analysis used MANOVA showed the p value of speaking ability was less than 0,05 which is 0.000 and for the value speaking anxiety was 0.000 < 0,05. It can be concluded that the CLT method gave the significant effect on the students, speaking ability and the CLT method also reduced students’ speaking anxiety.